Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1111/j.1442-200x.1997.tb03668.x
|View full text |Cite
|
Sign up to set email alerts
|

Early cardiac failure in a child with Becker muscular dystrophy is due to an abnormally low amount of dystrophin transcript lacking exon 13

Abstract: Two Japanese brothers with Becker muscular dystrophy were shown by polymerase chain reaction (PCR) and cDNA sequence analysis to produce a dystrophin gene transcript lacking a single exon; that is, number 13. Despite having the same deletion mutation, the brothers showed clearly different clinical phenotypes: the younger brother developed cardiac failure at the age of nine, while the elder brother was asymptomatic. As alternative splicing was not responsible for this clinical difference, the amount of dystroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…For example, the mRNA level for dystrophin was reduced with aging. In humans, the cardiomyopathies associated with Duchenne muscular dystrophy (19), Becker muscular dystrophy (20) and X-linked dilated cardiomyopathy are all caused by defects in the dystrophin gene (21). Since dystrophin-de®cient mice have an increased vulnerability to acute pressure overload in vivo the aging-associated reduced dystrophin mRNA level might contribute to a reduced threshold for the development of contractile dysfunction upon exposure to increased levels of mechanical stress (22).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the mRNA level for dystrophin was reduced with aging. In humans, the cardiomyopathies associated with Duchenne muscular dystrophy (19), Becker muscular dystrophy (20) and X-linked dilated cardiomyopathy are all caused by defects in the dystrophin gene (21). Since dystrophin-de®cient mice have an increased vulnerability to acute pressure overload in vivo the aging-associated reduced dystrophin mRNA level might contribute to a reduced threshold for the development of contractile dysfunction upon exposure to increased levels of mechanical stress (22).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 19 patients with BMD (20), six of whom were younger than 22 years of age, two had exertional dyspnea. In a report (21) of two brothers with a deletion of exon 13, one developed heart failure at nine years of age, while the older brother was asymptomatic. The different phenotypes were attributed to the amount of dystrophin transcript in the younger brother, which was 20% of that of the older brother.…”
Section: Diagnosis Of CI In Bmdmentioning
confidence: 99%
“…12 Genetic analysis showed that certain mutations seem to be associated with unique cardiac phenotypes at presentation (eg, missense rod domain lamin A/C mutations in autosomal dominant Emery-Dreifuss muscular dystrophy and A to G tRNA mutations in mitochondrial myopathy). 12,13 Despite the high incidence of cardiomyopathy in muscular dystrophies, such as myotonic dystrophy [14][15][16] and dystrophinopathies, 17,18 cases presenting initially with cardiac symptoms appear to be rare. Cardiac involvement generally increases with the progression of muscular dystrophies but some patients remain without cardiac symptoms for many years after the initial presentation of systemic weakness.…”
Section: Review Of Literaturementioning
confidence: 99%